2021
DOI: 10.3389/fpsyt.2021.624398
|View full text |Cite
|
Sign up to set email alerts
|

Completed Suicide With Violent and Non-violent Methods by the Elderly in Rural China: A Psychological Autopsy Study

Abstract: Background: Late-life suicide is a severe public health problem in rural China; however, knowledge regarding the specific characteristics and risk factors for completed suicide via violent and non-violent methods among elderly individuals in rural China is limited.Methods: Subjects aged 60 years or older were selected from rural areas in Shandong, Hunan, and Guangxi provinces in China. This study was a 1:1 matched case-control design conducted by using the psychological autopsy method.Results: According to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Diet may have a lesser impact on suicidal ideation than social factors. Indeed, according to earlier surveys, unhappy marriages, inadequate education, and economic poverty are significant social factors contributing to older adults' suicide (24,25). Furthermore, our gender stratification results indicate that both men and women in the High-DII group are at higher risk of developing depression than those in the Low-DII group.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Diet may have a lesser impact on suicidal ideation than social factors. Indeed, according to earlier surveys, unhappy marriages, inadequate education, and economic poverty are significant social factors contributing to older adults' suicide (24,25). Furthermore, our gender stratification results indicate that both men and women in the High-DII group are at higher risk of developing depression than those in the Low-DII group.…”
Section: Discussionmentioning
confidence: 52%
“…Diet may have a lesser impact on suicidal ideation than social factors. Indeed, according to earlier surveys, unhappy marriages, inadequate education, and economic poverty are significant social factors contributing to older adults’ suicide ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Sun et al reported the presence of seasonality among non-violent suicide cases [ 33 ]. A psychological autopsy study comparing violent and non-violent suicides among elderly individuals in rural China found that non-violent suicide cases had higher levels of depression compared to violent suicide cases and emphasized that depression and hopelessness were independent risk factors for non-violent suicide [ 26 ]. Considering that depression and hopelessness are risk factors for suicidal ideation and death [ 34 ], it is possible that non-violent suicide cases may be more vulnerable to environmental factors such as PM.…”
Section: Discussionmentioning
confidence: 99%
“…Violent methods included hanging, jumping from a height, jumping in front of a car or train, cutting and piercing with sharp objects, using firearms or shotguns, and self-immolation. Non-violent methods included ingestion of pesticides, drug overdose, gas poisoning, and suffocation [ 26 ]. In addition, the main cause of suicide was recorded as the factor that caused severe pain to the person who committed suicide and had the strongest influence on suicide among the stress factors that lasted until death by reviewing the investigation records.…”
Section: Methodsmentioning
confidence: 99%
“…From a medico‐legal point of view, for suicidal ideation is meant to have expressed verbally to someone the intent to die by suicide; instead, for previous suicide attempts is meant to have put in place concrete self‐harming actions of such severity as to be fatal. As for the method, it was divided into violent and nonviolent (Zhu et al, 2021): violent methods are hanging, drowning, use of a firearm or shotgun, cutting and piercing with sharp objects, jumping from high places, and being hit by a train or other vehicle; nonviolent methods are ingestion of pesticides, gas poisoning, suffocation, and drug overdose. For all the cases, a distinction was made between “simple suicides” and “complex suicides” (Bohnert, 2005; Gentile et al, 2021; Marcinkowski et al, 1974), that is, between suicides implemented through the application of a single injurious modality, and those implemented with the simultaneous or in the chronological succession application of more than one modality.…”
Section: Methodsmentioning
confidence: 99%